Unraveling the redox code to improve physiological research in human health and disease - Josh Thorley (Physiological Reports)
Abstract Redox reactions, involving electron transfer, are critical to human physiology. However, progress in understanding redox metabolism is hindered by flawed analytical methods. This review highlights emerging techniques that promise to revolutionize redox research, enhancing our comprehension of human health and disease. Oxygen, vital for aerobic metabolism, also produces reactive oxygen species (ROS), such as superoxide and hydrogen peroxide. While historically seen as harmful, ROS at low concentrations are now recognized as key regulators of cell signaling. A balance between ROS and antioxidants, known as redox balance, is crucial, and deviations can lead to oxidative stress. Recent studies have distinguished beneficial “oxidative eustress” from harmful “oxidative distress.” New techniques, such as advanced mass spectrometry and high‐throughput immunoassays, offer improved accuracy in measuring redox states and oxidative damage. These advancements are pivotal for understanding redox signaling, cysteine oxidation, and their implications for disease. Looking ahead, the development of precision redox medicine could lead to better treatments for oxidative stress‐related diseases and foster interventions promoting health.